A Study of Knowledge, Attitude and Practice (KAP) Regarding Voluntary Blood Donation among Health Care Professionals in Dhiraj Hospital- Vadodara - R. K. Tandon; Gunjan Rathod; Raxitkumar Suthar; Ashu Dogra (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Blood components like PCV, Whole Blood, Fresh Frozen Plasma(FFP), Platelet RichPlasma(PRP), Cryoprecipitate demands are increasing day by day in developing countries like India.So in our study to assess the overall knowledge, attitude and practice regarding the extent of blooddonation practice among health care workers have keen importance.Methods and Material: Our study which is a cross sectional study includes total of around 80 health careworkers of Dhiraj Hospital - Vadodara. On the basis of socio-demographic characteristics and accordingto the levels of Knowledge, Attitude and Practice among participants data were collected using a self –administered questionnaire. A structured questionnaire was given to all the health care workers working inthe Dhiraj hospital were taken into consideration.Results: Eighty health care workers were involved in our study which was conducted at Dhiraj hospitalVadodara among which it was found that about 55% donated to serve for humanity. A large group of around15% were donating as a replacement for their kith and kin. Around 10% were because of self motivateddecisions. And on the other side the reasons for non-donation by non-donors was that nobody approached tothem and it constituted to about 6%. Around 57% non donated due to some health related reasons while restof them non donated due to fear of disease transmission and fear of needle which constituted to about 17%.Conclusions: The health care workers of Dhiraj hospital were having overall level of knowledge, attitudeand practice was satisfactory. Health Professionals, various hospitals and blood banks services are demandedto develop new ways so to make blood donation services more reliable and accessible